Explainable Analytics to Predict the Quality of Life in Patients with Prostate Cancer from Longitudinal Data. Issue 1 (31st December 2022) - Sharifi, Fatemeh; Mohammed, Emad; Crump, Trafford; Far, Behrouz H.
ABSTRACT: Prostate cancer (PCa) is a complicated cancer with high level of unexplained variability that might affect the patient's health-related quality of life (HRQoL). Using 2670 patients' information with 433 measures per patient, our objective is to identify the minimal set of important variables which can predict 1-year follow-up HRQoL for PCa patients while adding interpretability to the proposed model. We address three problems of dimension reduction, prediction, and interpretability by first developing deep neural networks on top of a clustering algorithm to extract minimal set of important variables of baseline visit. Second, we build a model to predict a 1-year follow-up of HRQoL for PCa patients using the extracted important baseline variables. Third, we utilize Bayesian networks method to provide insights into the proposed model results to discover the relationship between patients' baseline variables and their 1-year follow-up satisfaction. The results support the use of the proposed machine-learning technique as an essential tool in identifying potential baseline variables for predicting 1-year HRQoL. Furthermore, our approach to interpret the findings will help to establish guidelines for a better shared decision-making platform for PCa patients.